Caruncular lesions: A 16-year single centre review in the United Kingdom. Issue 2 (March 2023) - Yvon, Camille; Balamurugan, Thiagarajah; Bianchi, Eleonora; Lee, Han Bin; Mclean, Christopher
Background/Aims: To review the clinicopathological features of caruncle biopsies carried out at a district general hospital in the United Kingdom (UK), and compare with other centres where data has been published. Methods: Retrospective, single-centre, observational case series between 2004–2020. Results: A total of 31 lesions from 31 patients were analysed. 18 of 31 patients were men (58%), and the age ranged from 12 to 91 years. 13 different histopathological types of lesions were identified in our case series, including 9 melanocytic nevi (29%), 7 benign squamous papillomas (23%), 5 skin adnexal lesions (16%), 3 chronic inflammation (10%), 3 epithelial cysts (10%), 1 basal cell carcinoma (3%), 2 malignant melanomas (6%) and l lymphoproliferative disorder (3%). Pre-operative suspected diagnoses were often vague but correct in 12 of 18 cases (67%), where data was available. Conclusion: The uncommon nature and variety of caruncular lesions make the diagnostic process difficult. Our case series is the first reported in the UK, showing a slightly higher proportion of malignant melanomas, in keeping with the population demographics. Excisional biopsies would, therefore, be prudent in the majority of cases to rule out any possible malignancy.